FUNGAL DISEASES OF ASPARAGUS VIGNA IN THE SOUTH OF WESTERN SIBERIA - Yu. V. Fotev; O. A. Kazakova (Овощи России)
Increasing popularity of asparagus bean (Vigna unguiculata (L.) Walp.) − a new for Russia vegetable crop requires comprehensive study including resistance to biotic environmental factors. Composition of pathogens of germinating seeds, plants (roots, leaves, stems, fruits) of large collection of asparagus bean from the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) and the Bioresource Scientific Collection of the CSBG SB RAS UNU No. USU 440534 have been investigated. Plants of 87 samples of asparagus bean were grown in the unheated plastic film greenhouse on the south of Western Siberia (54 ° N lat. 83 ° E) and examined for infestations of diseases in the Central Siberian Botanical Garden and Novosibirsk State Agrarian University (Novosibirsk). The infection of seeds with pathogenic micromycetes was determined according to GOST 12044-93 (similar to common beans) using the methods of mycological analysis and the Petri-dish moist chambers, also on Chapek media and KDA media. The main pathogenic micromycetes are: on germinating seeds − species of the genera Fusarium, Aspergillus, Penicillium, Alternaria, Mucor, Botrytis cinerea, Sclerotinia sclerotiorum; on seedlings − Fusarium solani; during fruiting on fruits and stems − B. cinerea and S. sclerotiorum; on the root collar − S. sclerotiorum. The dominant forms of white mold were stem, root collar, fruits. Five samples that showed a high level of resistance to B.cinerea and S.sclerotiorum have been selected. System for asparagus bean disease surveillance which should be built in the calendar-phenological sequence, has been recommended.